2003
DOI: 10.1213/01.ane.0000067400.79654.30
|View full text |Cite
|
Sign up to set email alerts
|

Aortocaval Compression in Pregnancy: The Effect of Changing the Degree and Direction of Lateral Tilt on Maternal Cardiac Output

Abstract: Using thoracic bioimpedance to measure maternal cardiac output, we were unable to demonstrate any benefit from increasing the magnitude of lateral table tilt. This implies that it is unnecessary to use extremes of lateral table tilt in healthy pregnancy although this may not apply to women with cardiac compromise or regional anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 18 publications
3
66
0
6
Order By: Relevance
“…The supine wedged position (wedge placed under the right hip) or a 12-15°l eft lateral tilt has been used to displace the gravid uterus and to minimise the effects of aortocaval compression. In a study comparing the effects of various tilts, however, up to 12.5°of left lateral tilt failed to produce any significant improvement in the cardiac output [9]. In the lateral position, the uterus is likely to be displaced away from the aorta and inferior vena cava, thereby avoiding aortocaval compression.…”
Section: Discussionmentioning
confidence: 98%
“…The supine wedged position (wedge placed under the right hip) or a 12-15°l eft lateral tilt has been used to displace the gravid uterus and to minimise the effects of aortocaval compression. In a study comparing the effects of various tilts, however, up to 12.5°of left lateral tilt failed to produce any significant improvement in the cardiac output [9]. In the lateral position, the uterus is likely to be displaced away from the aorta and inferior vena cava, thereby avoiding aortocaval compression.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Rees et al 16 supports these findings; they showed that even a true 15°left table tilt is associated with some aortic compression. In addition, Bamber et al 17 showed a reduction in stroke volume and cardiac output due to aortocaval compression by the gravid uterus when healthy pregnant women are rotated from the full lateral position to the right-tilted supine position. In the current study, the observed lack of difference in SBP between the study groups was anticipated a priori and could be explained by the prompt treatment of SBP deviations from baseline values to maintain patients' hemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%
“…13 Their findings could be explained in part by the higher dose of hyperbaric bupivacaine administered (0.5% hyperbaric bupivacaine 2.8 mL) and in part by the modest degree of lateral tilt used (10°), which has been associated with aortocaval compression. 17 Opponents of the sitting position also argue that vagal reflexes are more common in the sitting position, uterine perfusion is better in the lateral decubitus position, and due to a lower hydrostatic pressure, there is less likelihood of epidural vein puncture when neuraxial anesthesia is performed in the lateral position. 21 Furthermore, Patel et al 18 observed that the sitting position was associated with a higher incidence of inadequate block.…”
Section: Discussionmentioning
confidence: 99%
“…In the elective situation, the fetus is presumed to be uncompromised and is commonly unmonitored while the block develops. However, the tilted position is a compromise between the need for easy surgical access and the avoidance of the supine hypotensive syndrome, and several studies suggest that aortocaval compression may still occur in this position [1,2].A previous study found no difference in neonatal outcome (cord blood gases and Apgar scores) when comparing an estimated 208 tilt with the lateral position in women undergoing elective Caesarean section, but aortic compression was not assessed [3].The aims of this study were to compare the maternal and fetal effects of two positions, 158 left tilt and left lateral, following the initiation of spinal anaesthesia for elective Caesarean section. …”
mentioning
confidence: 99%